Demographic and Cultural Factors Influencing the Adoption of B2C E-Commerce in SCO Region - Sugarmaa Purevkhuu; Javkhlan Munkhbold (Green Publisher Indonesia, 2021)
In the era of digitalization, e-commerce is providing exceptional opportunities to access domestic and international markets and is believed to be one of the main tools for poverty reduction and development acceleration. Shanghai Cooperation Organization (SCO), as one of the main intergovernmental organizations in Eurasia, is taking measures to develop e-commerce in the region. However, SCO member states vary in terms of e-commerce experience due to dissimilar economic situations and cultural differences. The purpose of this paper is to examine the factors that affect B2C e-commerce adoption in the SCO region. The main objective of the study is to integrate the demographic characteristics with Hofstede’s cultural dimensions in order to determine the factors of e-commerce adoption among customers in SCO member states. The result shows that in SCO countries, e-commerce is more spread amongst young females who are currently employed, and therefore have high education levels and incomes. From the perspective of the national culture, SCO member countries with high individualism, low uncertainty avoidance, and low indulgence level have more e-commerce customers than the other SCO member states.